CHARACTERIZING COSMIC-RAY PROPAGATION IN MASSIVE STAR-FORMING REGIONS: THE CASE OF 30 DORADUS AND THE LARGE MAGELLANIC CLOUD - Murphy, E. J.; Porter, T. A.; Moskalenko, I. V.; Helou, G.; Strong, A. W. (The Astrophysical journal, 2012)
Using infrared, radio, and gamma -ray data, we investigate the propagation characteristics of cosmic-ray (CR) electrons and nuclei in the 30 Doradus (30 Dor) star-forming region in the Large Magellanic Cloud (LMC) using a phenomenological model based on the radio-far-infrared correlation within galaxies. We compare the values of the CR electron propagation length and surface brightness for 30 Dor and the LMC as a whole with those of entire disk galaxies. We find that the trend of decreasing average CR propagation distance with increasing disk-averaged star formation activity holds for the LMC, and extends down to single star-forming regions, at least for the case of 30 Dor.